Peran Kepuasan Dalam Memediasi Pengaruh Antara Biaya Pendidikan dan Kualitas Layanan Terhadap Wom - Mahadika, Komang (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
This study aims to analyze the role of satisfaction in mediating the effect between education costs and service quality on WOM (word of mouth). The sampling technique in this study is non-probability sampling using the purposive sampling method or often also called judge mental sampling, with 95 students active respondents from the Faculty of Business and Tourism for the 2022 UNTRIM period. Data processing of the results of this study using the Partial Least Square (PLS) Software method. The findings of this study show that the cost of education (X1) proved to have no effect on word of mouth (Y), Quality of service (X2) and student satisfaction (Z) had a positive and significant effect on word of mouth (Y), Tuition fees (X1) and Quality of service (X2) proved to have a positive and significant effect on student satisfaction (Z), student satisfaction (Z) had no effect in mediating the effect of tuition fees (X1) and services (X2) on word of mouth (Y). The implications of this research are expected to be used as a reference in future research, and can provide positive input for the progress of UNTRIM in the future.